2017
DOI: 10.1038/s41598-017-08070-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDE2 reverses beta amyloid induced memory impairment through regulation of PKA/PKG-dependent neuro-inflammatory and apoptotic pathways

Abstract: Beta amyloid peptides (Aβ) are known risk factors involved in cognitive impairment, neuroinflammatory and apoptotic processes in Alzheimer’s disease (AD). Phosphodiesterase 2 (PDE2) inhibitors increase the intracellular cAMP and/or cGMP activities, which may ameliorate cognitive deficits associated with AD. However, it remains unclear whether PDE2 mediated neuroapoptotic and neuroinflammatory events, as well as cognitive performance in AD are related to cAMP/cGMP-dependent pathways. The present study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…Our previous studies suggested that microinjection of Aβ into the CA1 induced decreased second messengers (cAMP and cGMP) in the hippocampus (Wang L. et al, 2017 ). As the enzymes that hydrolyze and inactivate the second messenger cAMP, PDE4 is found to be associated with memory regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies suggested that microinjection of Aβ into the CA1 induced decreased second messengers (cAMP and cGMP) in the hippocampus (Wang L. et al, 2017 ). As the enzymes that hydrolyze and inactivate the second messenger cAMP, PDE4 is found to be associated with memory regulation.…”
Section: Discussionmentioning
confidence: 97%
“…MAPK8IP2 is also known as JIP2, c-Jun NH(2)-terminal kinase (JNK)-interacting protein 2, which is known to interact with Aβ to play an important role in the metabolism and/or the function of Aβ including the regulation of Aβ phosphorylation by JNK [38]. Inhibition of PDE2 has been shown to rescue Aβ induced memory impairment via regulation of PKA/ PKG-dependent neuroinflammatory and apoptotic pathways [39]. Finally, genetic variants from BZRAP1-AS1 were previously implicated to be associated with AD [40].…”
mentioning
confidence: 99%
“…In addition to PDE9 inhibitors, other PDE inhibitors also affect LTP-related plasticity (Heckman et al, 2015; Puzzo et al, 2008; Reneerkens et al, 2009). Specific inhibitors of PDE1 (Snyder et al, 2016), PDE2 (Boess et al, 2004; Wang et al, 2017), PDE3 (Hiramatsu et al, 2010), PDE4 (Bruno et al, 2011; Ricciarelli et al, 2017), PDE5 (Prickaerts et al, 1997; Prickaerts et al, 2002b), PDE7 (Perez-Gonzalez et al, 2013), and PDE9 (Hutson et al, 2011; van der Staay et al, 2008) have been shown to enhance memory performance in rodent. For example, the selective PDE2 inhibitor BAY 60-7550 improves memory acquisition and consolidation in the object recognition task (Boess et al, 2004; Domek-Lopacinska et al, 2008; Rutten et al, 2007), and reverses the deficit in object recognition produced by acute tryptophan depletion (van Donkelaar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%